2020
DOI: 10.1016/j.ejpn.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Seizures during treatment of childhood acute lymphoblastic leukemia: A population-based cohort study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 43 publications
4
32
1
Order By: Relevance
“…In our study, patients with T-cell ALL and CNS leukemia had higher risk for admission to the ICU, but we could not show association with higher ICU mortality. CNS leukemia and T-cell immunophenotype have been associated with acute CNS toxicity, increased need for intensive care, and thrombosis (23)(24)(25)(26). A previous Nordic study showed that patients with T-cell ALL had higher risk for treatment-related mortality, but this could not be demonstrated in another large study from the United States (5,27).…”
Section: At the Bedsidementioning
confidence: 99%
“…In our study, patients with T-cell ALL and CNS leukemia had higher risk for admission to the ICU, but we could not show association with higher ICU mortality. CNS leukemia and T-cell immunophenotype have been associated with acute CNS toxicity, increased need for intensive care, and thrombosis (23)(24)(25)(26). A previous Nordic study showed that patients with T-cell ALL had higher risk for treatment-related mortality, but this could not be demonstrated in another large study from the United States (5,27).…”
Section: At the Bedsidementioning
confidence: 99%
“…According to statistics, epileptic seizures occurred in 8 ~ 13% of ALL patients during treatment ( 6 ). There is a higher risk of late neurological complications in ALL patients with epilepsy than those without epilepsy, leading to symptomatic epilepsy and mental retardation ( 7 ). It is not only beneficial to timely and effective treatment and avoid irreversible damage, but also affects the choice of follow-up chemotherapy and the prognosis of nervous system in children with ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Children aged between 1 and 17.9 years, diagnosed with ALL between Patients with data on CSF by FCI at diagnosis were identified from a previous study and combined with registry data. 4,7,10 Patients with ≥10 blasts in the CSF by FCI were defined as having CNS involvement (CNS flow+ ) and patients with <10 blasts in the CSF were defined as not having CNS involvement (CNS flow-). 4 Statistical analyses were performed using SPSS, version 26.0.…”
Section: Methodsmentioning
confidence: 99%
“…Children aged between 1 and 17.9 years, diagnosed with ALL between 2008 and 2015 and treated according to the Nordic Society of Paediatric Haematology and Oncology (NOPHO) ALL2008 protocol, with data from diagnostic lumbar puncture by both CSF FCI and CM, were included. Patients with CNS toxicities were identified through a prospective online registration system 1,7,10 . CNS toxicities were grouped into three categories: “all CNS toxicities” including patients with any CNS toxicity, “seizures” including patients with isolated seizures and those with seizures secondary to other CNS toxicity, and “PRES.”…”
Section: Methodsmentioning
confidence: 99%